2017
DOI: 10.1111/fwb.12936
|View full text |Cite
|
Sign up to set email alerts
|

Species richness and taxonomic distinctness of lake macrophytes along environmental gradients in two continents

Abstract: The biodiversity of aquatic ecosystems is under threat and there is an urgent need to quantify the various facets of biodiversity to assess the conservation value of freshwater ecosystems. The effects of taxonomic relatedness have so far not been taken into account in biodiversity assessments of lake macrophytes. We therefore tested the response of species richness and average taxonomic distinctness (AvTD) of aquatic macrophytes along environmental gradients using linear regression models and Bayesian Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 82 publications
(189 reference statements)
1
14
0
Order By: Relevance
“…This indicates that regardless of community drivers related to the reef environment, the composition of the coral microbiome system is structured at the individual level. The structure and complexity of the assemblage, expressed as taxonomic relatedness (average of taxonomic distinctness [Δ + ]) ( 32 ) and taxonomic evenness (variation of taxonomic distinctness [Λ + ]) ( 33 ), provide a measure of the taxonomic spread of communities ( 34 ) which has been applied in macroecology ( 35 37 ) and more recently utilized in microbial ecology ( 38 , 39 ). This allows us to assess biodiversity changes on spatial and temporal scales and the response to disturbances.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that regardless of community drivers related to the reef environment, the composition of the coral microbiome system is structured at the individual level. The structure and complexity of the assemblage, expressed as taxonomic relatedness (average of taxonomic distinctness [Δ + ]) ( 32 ) and taxonomic evenness (variation of taxonomic distinctness [Λ + ]) ( 33 ), provide a measure of the taxonomic spread of communities ( 34 ) which has been applied in macroecology ( 35 37 ) and more recently utilized in microbial ecology ( 38 , 39 ). This allows us to assess biodiversity changes on spatial and temporal scales and the response to disturbances.…”
Section: Resultsmentioning
confidence: 99%
“…The response of macrophyte richness to total phosphorus is frequently unimodal, decreasing [62] or increasing with eutrophication [67], which is probably hiding a more general hump-shaped relationship (low richness in oligotrophic, high richness in mesotrophic, and low richness in hypereutrophic lakes) [68]. These relations can also vary across regions or contexts [69] and macrophyte growth-forms [63]. Our results showed no correlation between total phosphorus and macrophyte species richness, probably due to the low phosphorus concentrations found in most of our SSL.…”
Section: Drivers Of Macrophyte Species Richnessmentioning
confidence: 99%
“…Contrary to our second hypothesis, we did not establish a correlation between aquatic plant richness and climate (neither with mean annual temperature nor with elevation). Several studies have demonstrated a linear decrease or negative correlation of macrophyte species richness with altitude [63,70,71], probably depending on the strength of elevational gradient [72]. However, some other studies failed to demonstrate a clear pattern between floristic richness and altitude [34,73].…”
Section: Drivers Of Macrophyte Species Richnessmentioning
confidence: 99%
“…S2). After the introduction of taxonomic distinctness index as a proxy of phylogeny (Clarke and Warwick 2001), there were several papers published where taxonomic distinctness of macroinvertebrates was correlated with environmental variables (e.g., Abellan et al 2006;Heino et al 2007;Alahuhta et al 2017a).…”
Section: Percentage Of Papersmentioning
confidence: 99%
“…For example, Bhat and Magurran (2006) first reported that the indices of phylogenetic relatedness may be masked by influences of habitat variability on fish species compositions in India. Subsequently, other studies have found that natural environmental characteristics may overshadow the influences of anthropogenic pressures on taxonomic distinctness (Heino et al 2007;Alahuhta et al 2017a). In addition, the performance and ability to detect humaninduced stress of taxonomic distinctness may depend on the phylogenetic structure of surveyed taxa within a study region, as well as their evolutionary and ecological history (Abellan et al 2006).…”
Section: Environmental Change Drives Biodiversity Patterns In Freshwamentioning
confidence: 99%